Pembuatan Biodigester Type Batch Skala 120 Liter untuk menghasilkan Biogas dari Campuran Bahan Baku Kotoran Kambing, Kotoran Ayam dan Limbah Sayur - Popi Febrianti; Nadiareta Sitorus; Desniorita Desniorita; Miftahurrahmah Miftahurrahmah (Jurnal Sains dan Teknologi, 2024)
Biogas is a potential renewable energy source to meet energy needs, especially in remote areas that do not have access to electricity. The process of making biogas is carried out through anaerobic fermentation of organic materials such as vegetable waste, livestock manure and agricultural waste. This research aims to design a batch type biodigester that can produce biogas from a mixture of goat manure, chicken manure and vegetable waste. Biodigester is a reactor used to produce biogas. The stirred biodigester aims to mix the substrate evenly in the biodigester and prevent the formation of scum. The biodigester designed has a capacity of 120 liters with a stirring system to increase the efficiency of biogas production. The fermentation process was carried out for 21 days by monitoring parameters such as temperature, pH, Chemical Oxygen Demand (COD), and methane gas concentration (CH4). The results showed that the temperature and pH in the biodigester remained in optimal conditions for the activity of methanogenic microorganisms. The highest CH4 concentration measurement was recorded on day 20 at 60%, which indicates good biogas quality. In addition, the flame test on day 21 produced a blue flame, indicating a high CH4 content. The decrease in CH4 concentration at the end of the study was caused by the exhaustion of organic material. This research contributes to the development of efficient and environmentally friendly biodigester technology to produce biogas as a renewable energy source.